Early Height and Weight Changes in Children Using Cotrimoxazole Prophylaxis with Antiretroviral Therapy - David C. Boettiger (2018)
© The Author 2016. Background. The growth benefits of cotrimoxazole during early antiretroviral therapy (ART) are not well characterized. Methods. Individuals enrolled in the Therapeutics Research, Education, and AIDS Training in Asia Pediatric HIV Observational Database were included if they started ART at ages 1 month-14 years and had both height and weight measurements available at ART initiation (baseline). Generalized estimating equations were used to identify factors associated with change in height-for-age z-score (HAZ), follow-up HAZ ≥ -2, change in weight-for-age z-score (WAZ), and follow-up WAZ ≥ -2. Results. A total of 3217 children were eligible for analysis. The adjusted mean change in HAZ among cotrimoxazole and non-cotrimoxazole users did not differ significantly over the first 24 months of ART. In children who were stunted (HAZ < -2) at baseline, cotrimoxazole use was not associated with a follow-up HAZ ≥ -2. The adjusted mean change in WAZ among children with a baseline CD4 percentage (CD4%) >25% became significantly different between cotrimoxazole and non-cotrimoxazole users after 6 months of ART and remained significant after 24 months (overall P <. 01). Similar changes in WAZ were observed in those with a baseline CD4% between 10% and 24% (overall P <. 01). Cotrimoxazole use was not associated with a significant difference in follow-up WAZ in children with a baseline CD4% <10%. In those underweight (WAZ < -2) at baseline, cotrimoxazole use was associated with a follow-up WAZ ≥ -2 (adjusted odds ratio, 1.70 vs not using cotrimoxazole [95% confidence interval, 1.28-2.25], P <. 01). This association was driven by children with a baseline CD4% ≥10%. Conclusions. Cotrimoxazole use is associated with benefits to WAZ but not HAZ during early ART in Asian children.